2012
DOI: 10.1063/1.4711147
|View full text |Cite
|
Sign up to set email alerts
|

How to calculate tortuosity easily?

Abstract: Tortuosity is one of the key parameters describing the geometry and transport properties of porous media. It is defined either as an average elongation of fluid paths or as a retardation factor that measures the resistance of a porous medium to the flow. However, in contrast to a retardation factor, an average fluid path elongation is difficult to compute numerically and, in general, is not measurable directly in experiments. We review some recent achievements in bridging the gap between the two formulations o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 21 publications
1
46
0
4
Order By: Relevance
“…4a for D A = 9.8 × 10 −10 m 2 /s and D B (m 2 /s) = 5.8 × 10 −7 = ffiffiffiffiffiffiffi tðsÞ p . The diffusivity of A in the precipitate was estimated from its molecular diffusivity in solution D A∞ = 5.3 × 10 −9 m 2 /s, the measured porosity of the precipitate ϕ = 0.52, and its tortuosity τ = 2.8, as D A = ϕD A∞ =τ; the relatively high value for the tortuosity is consistent with a precipitate composed of channels at an angle of ∼ 20°to the membrane surface (30). For the transport of B in the gel layer, we need to consider hydrodynamic effects.…”
Section: Model and Comparison With Experimentsmentioning
confidence: 99%
“…4a for D A = 9.8 × 10 −10 m 2 /s and D B (m 2 /s) = 5.8 × 10 −7 = ffiffiffiffiffiffiffi tðsÞ p . The diffusivity of A in the precipitate was estimated from its molecular diffusivity in solution D A∞ = 5.3 × 10 −9 m 2 /s, the measured porosity of the precipitate ϕ = 0.52, and its tortuosity τ = 2.8, as D A = ϕD A∞ =τ; the relatively high value for the tortuosity is consistent with a precipitate composed of channels at an angle of ∼ 20°to the membrane surface (30). For the transport of B in the gel layer, we need to consider hydrodynamic effects.…”
Section: Model and Comparison With Experimentsmentioning
confidence: 99%
“…Furthermore, for higher misalignment, it is found that pinning is clearly stronger in the case of narrower necks and smaller periods (results not shown for brevity). We also consider the tortuosity (Duda et al, 2011;Matyka & Koza, 2012). The tortuosity is a measure of the departure of fluid flow from straight pathways.…”
Section: Sinusoidal Profilesmentioning
confidence: 99%
“…The tortuosity is a measure of the departure of fluid flow from straight pathways. The calculations are made by means of the formula λ = < u > / < u x > (Duda et al, 2011;Matyka & Koza, 2012), u being the overall fluid velocity Shan & Chen, 1993;Shan & Doolen, 1995). It should be kept in mind that at the interface there are spurious currents (Wagner, 2003).…”
Section: Sinusoidal Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another quantity that is taken into account is the tortuosity (Bear, 1972) which is defined as the ratio of the actual length of the capillary paths to the corresponding length of the sample. The formula u / u x (Duda, Koza, & Matyka, 2011;Matyka & Koza, 2012) is used for the computations, where u is the magnitude of the fluid velocity of the components u x and u y . It is worth recalling that at the interface there are spurious currents (Wagner, 2003).…”
Section: Models and Analysismentioning
confidence: 99%